To destroy or not? A Cognitive Linguistics exploration of Yahweh’s (un)willingness to destroy Israel in Deuteronomy - Izaak J.L. Connoway (In die Skriflig)
Deuteronomy portrays Yahweh as both willing (e.g. Dt 28:63) and unwilling (Dt 4:31; 10:10) to destroy Israel, which creates one tension worthy of exploration. Of the three most prominent verbs of destruction, two [שׁמד and אבד] are constantly used in affirmative statements, and one [שׁחת] is continuously negated. However, these elude being divided into two levels of severity. Beyond that, in some verses (e.g. Dt 4:26) it appears that Israel is threatened with annihilation for idolatry after they cross the Jordan while their continued existence is also noted in the context, which creates another tension worthy of exploration. Secondary literature does not always seem aware of these tensions or the need to address them. This article sought to explore the tensions of Yahweh’s willingness and unwillingness to destroy Israel and whether the annihilation of Israel is in view in these verses (e.g. Dt 4:6), as well as the role these verbs play in these matters. This study used a literary approach for secondary sources. A theory-driven data-informed method of analysis and Discourse Analysis, both emanating from Cognitive Linguistics (CL), were used to analyse the Hebrew text. The study found that when שׁמד and אבד are used for future judgement for idolatry once Israel crosses the Jordan (e.g. Dt 4:26), they never refer to the annihilation of Israel. Although the judgement described there does involve severe casualties, the focus is on being removed from Canaan rather than the nation being annihilated. In Deuteronomy 9, however, שׁמד does refer to annihilation since it is coordinated with verbs of annihilation, indicating Yahweh’s intent to wipe Israel out at Horeb.